Correlation between cardiovascular diseases and periodontitis - a retrospective study - V, PADMAHARISH; RAJENDRAN, DEEPIKA; G, DEEPA (The journal of contemporary issues in business and government, 2021)
Periodontitis is a chronic inflammatory disease caused by bacterial colonization, which results in destruction of the tissues between the tooth surface and gingiva, loss of connective tissue attachment, erosion of alveolar bone, and tooth loss. There is much evidence stating that prevalent periodontitis is associated with increased coronary heart disease risk. Thus there is a need to evaluate the extent to which the strength of this association has been established. The aim of this study was to evaluate the correlation between cardiovascular diseases and periodontitis. A retrospective study was conducted using the patient records from a private dental college from June 2019 - March 2020. The study population included the case records of cardiovascular disease patients, selected by non-probability purposive sampling. Data was collected and then subjected to statistical analysis. Microsoft Excel 2016 (Microsoft office 10) data spreadsheet was used to collect data and later exported to SPSS IBM (version 20.0). Descriptive statistics and chi square test were employed with a level of significance set at p<0.05. The prevalence of periodontitis among cardiovascular patients was 81.47%. Among patients with CVD, 78.06% of hypertension patients, 3.41% of MI patients and 0.22% patients with other cardiac diseases had periodontitis. Within the limits of this study, there was a significant correlation between CVD and periodontitis (p=0.000), with a higher prevalence among hypertension patients. Patients with periodontitis are at an increased risk for cardiovascular diseases. The systemic inflammatory or immune response to periodontal infection may increase cardiovascular risk. Thus proper oral hygiene practices are important in maintaining overall health.